2008
DOI: 10.1007/s12119-007-9019-1
|View full text |Cite
|
Sign up to set email alerts
|

“Can Women Have Sex Like a Man?”: Sexual Scripts in Sex and the City

Abstract: The television series Sex and the City became an instant international hit from its 1998 debut on HBO throughout its final episode in 2004 and still remains popular through syndication and DVD sales and rentals. The series garnered widespread attention due to its explicit depiction and candid discussion of female sexuality. Sex and the City challenges commonly held cultural beliefs about what constitutes appropriate sexual desires and behaviors for women. According to sexual script theory, sexuality is not inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…Traditional gendered scripts of sexual aggressiveness for men and of passiveness, gate-keeping, and relationship prioritizing and maintenance for women are common in media (Kim et al, 2007). Even the show named in several of our study narratives as particularly informative, Sex and the City, has been found to ultimately conform to the traditionally gendered script of women as relationship maintainers (Markle, 2008). Women also mentioned sex toy parties with peers as an important context for peer interactions about masturbation.…”
Section: Discussionmentioning
confidence: 69%
“…Traditional gendered scripts of sexual aggressiveness for men and of passiveness, gate-keeping, and relationship prioritizing and maintenance for women are common in media (Kim et al, 2007). Even the show named in several of our study narratives as particularly informative, Sex and the City, has been found to ultimately conform to the traditionally gendered script of women as relationship maintainers (Markle, 2008). Women also mentioned sex toy parties with peers as an important context for peer interactions about masturbation.…”
Section: Discussionmentioning
confidence: 69%
“…The use of a gender binary framework results in differential upbringing of boys and girls, which provides the foundation for the dichotomous development of traditional sexual scripts for men and women (Simon & Gagnon, 1969;Wiederman, 2005). Prescribed gender roles for men and women are rigid and pervasive in the media and the general population (Eaton & Rose, 2011;Markle, 2008;Ménard & Cabrera, 2011). Individuals speak about sex and sexuality in a way that corresponds with traditional gendered cultural scenarios, but individual experiences are not necessarily congruent (McCabe, Tanner and Heiman, 2010).…”
Section: Heterosexual Sexual Scriptsmentioning
confidence: 99%
“…Das zeigten Greenberg und D'Alessio (1985) anhand einer Inhaltsanalyse von je drei Folgen aus 13 Soaps. Eine Untersuchung von 37 Folgen der international erfolgreichen Serie "Sex and the City" aus den 2000er Jahren zeigte ein anderes Bild (Markle 2008): In der Serie, die sich um eine Freundesgruppe sexuell aktiver Frauen dreht, herrschte ein Gleichverhältnis dahingehend, wie oft Frauen und Männer Sex initiierten oder ablehnten. Im deutschsprachigen Raum zeigte eine Inhaltsanalyse von 69 Softsex-Spielfilmen der privaten Sender RTL und Sat.1 (Brosius und Rössler 1999), dass die Initiative zum Geschlechtsverkehr genauso häufig von Frauen wie von Männern ausgeht.…”
Section: Initiation Von Geschlechtsverkehrunclassified